EFEKTIVITAS PEMBELAJARAN LUAR KELAS PADA MATERI KENAMPAKAN ALAM TERHADAP HASIL BELAJAR DAN KETERAMPILAN KERJASAMA SISWA SD KELAS IV - nurdin kamil; Siti Dewi Maharani (Universitas Sriwijaya, 2023)
Learning in the 21st Century contains learning designs that are able to explore students' abilities. Out-of-class learning that invites students to develop knowledge and skills becomes an alternative in the developed learning design. This research is a study that aims to see the effectiveness of out-of-class learning on natural appearance material on student learning outcomes and cooperation skills. This study used quantitative research methods with a quasi-experimental design. This study used One Group Pretest-Posttest design with data collection techniques in the form of tests and non-tests. Data analysis techniques use prerequisite tests and t tests (independent T-test). The results of this study showed that the calculation results obtained tcount = 32.99 while ttable = 1.68 at a 95% confidence level or error rate, ?. = 5%. Based on the results of these calculations, it can be seen that tcalculate > ttable. Therefore ,h-0. rejected and ,h-a. accepted so that it can be stated that there is a difference between the pretest and posttest learning outcomes of students. The results of descriptive statistical analysis showed that after the application of the out-of-class learning model, the score of the applied Cooperation skills received an average score of 87.3. Whereas before being given the Cooperation skills treatment, students had an average score of 59.7. This shows that there is an increase in student cooperation in learning using out-of-class learning models.